1996
DOI: 10.1038/383275a0
|View full text |Cite
|
Sign up to set email alerts
|

Unique fold and active site in cytomegalovirus protease

Abstract: Human herpesviruses are responsible for a variety of diseases. They are divided into three subfamilies: alpha includes herpes simplex viruses (HSV-1 and HSV-2) and varicella-zoster virus (VZV); beta includes cytomegalovirus (CMV) and human herpesvirus-6 (HHV-6); and gamma includes Epstein-Barr virus (EBV). Each virus encodes a serine protease that is essential for its replication and is a potential target for therapeutic intervention. Human CMV is a ubiquitous opportunistic pathogen that can result in life-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 22 publications
4
124
0
Order By: Relevance
“…Among these are the proteinase and assembly proteins, both of which play essential roles in capsid assembly and maturation (Preston et al, 1983 ;Gao et al, 1994). They have been characterized from herpes simplex virus type 1 (HSV-1), human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) (Gibson et al, 1994 ;Donaghy & Jupp, 1995) and the three-dimensional structure of the HCMV proteinase has recently been solved (Chen et al, 1996 ;Qiu et al, 1996 ;Shieh et al, 1996 ;Tong et al, 1996). Sequence homology suggests that VZV genes 33 and 33.5 encode the VZV proteinase and assembly protein respectively (Welch et al, 1991 ;Gibson et al, 1994).…”
Section: Varicella-zoster Virus (Vzv) Is a Member Of Thementioning
confidence: 99%
“…Among these are the proteinase and assembly proteins, both of which play essential roles in capsid assembly and maturation (Preston et al, 1983 ;Gao et al, 1994). They have been characterized from herpes simplex virus type 1 (HSV-1), human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) (Gibson et al, 1994 ;Donaghy & Jupp, 1995) and the three-dimensional structure of the HCMV proteinase has recently been solved (Chen et al, 1996 ;Qiu et al, 1996 ;Shieh et al, 1996 ;Tong et al, 1996). Sequence homology suggests that VZV genes 33 and 33.5 encode the VZV proteinase and assembly protein respectively (Welch et al, 1991 ;Gibson et al, 1994).…”
Section: Varicella-zoster Virus (Vzv) Is a Member Of Thementioning
confidence: 99%
“…The amino-acid sequences of herpesvirus proteases have no detectable homology to other serine proteases or hydrolases. The crystal structure of HCMV protease has recently been determined in our laboratory by the seleno-methionyl multiple-wavelength anomalous diffraction (MAD) technique (Tong et al, 1996), and in other laboratories by the heavy-atom isomorphous replacement technique (Qiu et al, 1996;Shieh et al, 1996;Chen et al, 1996). It showed that HCMV protease possesses a new polypeptide backbone fold; confirmed that Ser132 and His63 are in close proximity in space; and identified His157 as the possible third member of the catalytic triad.…”
Section: Introductionmentioning
confidence: 94%
“…The first crystal structures of an assemblin were published by three groups in 1996 [58,59,83]. All three structures are of dimeric HCMV-assemblin.…”
Section: Structurementioning
confidence: 99%